HISTOPATOLOGI AORTA TORASIKA Rattus novergicus STRAIN WISTAR JANTAN SETELAH 8 MINGGU PEMBERIAN DIET ATEROGENIK - Welinsa, Fatya; Asni, Enikarmila; Malik, Zulkifli (Jurnal Online Mahasiswa (JOM) Bidang Kedokteran, 2015)
ABSTRACTAtherosclerosis could be induced in animal model (Rattus novergicus) by feeding atherogenic diet consist of standart feed, cholesterol 2 % from yolk, 5 % goat fat, 0,2% cholic acid and induction with vitamin D3. The goal of this research was to analyze histopathological of thoracic aorta on male Rattus novergicus strain wistar after fed atherogenic diet for 8 weeks. This research was an experimental laboratory research with post test only with control design. Twelve male rats were segregated into two groups (n=6) labelled as control fed standart and atherogenic fed group. After 8 weeks thoracic aorta was taken and histological slides were made and colored with hematoxylin eosin and then measured with atherosclerosis score. The result showed that in atherogenic group there are macrophage, foam cell, and intracellular lipid accumulation with 100% percentage, extracellular lipid accumulation 33,33% (for a little extracellular lipid) and 66,67 (a lot of extracellular lipid) while control group there are macrophage, foam cell, and intracellular lipid accumulation with 33,33% percentage. The statistical test result show there is significant difference between control group and atherogenic group (p=0,003). As conclusion, there is significant difference between control group and atherogenic group.Keywords : Atherosclerosis, atherogenic diet, thoracic aorta